Auto-Referenciação em Jogos Retro: Uma Framework - Guilherme Vasconcelos Alves de Lima (2020)
Retro games have as one of their main structural elements the representation of classic games, technologies and past platforms. This dissertation proposes the development of a framework based on the characteristic of self-referencing exercised by retro games as media in order to assist in the design of retro games and in the identification of fundamental principles to the experience of playing these games. Considering that retro games have an implied player, this work proposes the creation of a design tool focused on the key principles related to experience design. Twenty retro games were analyzed and different types of referencing used by video games were identified: mechanic, dynamic, aesthetic and narrative. These typologies allowed different functionalities to be analyzed for each application. In addition, the elements that fundamentally represent the retro style were identified and analyzed. The framework was responsible for allowing the identified principles to be used in a retro game design canvas format based on self-referencing. This dissertation proposes that the analysis of self-referencing is considered an essential resource for the design of retro gaming experiences. It is intended that the results achieved can contribute to the conception and experience design of this category of video games. Keywords: Design, Experience, Framework, Nostalgia, Retro, Referencing, Video Games.